Region of Interest (ROI) for EEG Activity in Depressed Young Adult - Zi Xiang, Lim; Fauzan, Norsiah (International Journal of Engineering and Technology, 2018)
Several abnormal neural activities in regions such as dorsolateral prefrontal cortex (DLPFC) and prefrontal cortex (PFC) are known to be associated with depression. However most studies focused on major depression disorder and less on mild and moderate depression, moreover, these studies are mostly conducted in United State and European countries. This study uses data from 12 mild and moderately depressed and 12 healthy control young adult in Malaysia to examine the differences in brain activity via spectrum and coherence analysis in quantitative electroencephalography (qEEG). The study found that depressed group have higher beta on the anterior region that is found on people with depression and recurrent depression in previous studies, and higher theta on the prefrontal cortex may associate with deficits in attention and working memory in resting state compare to healthy control. Furthermore, left and right frontal showed low beta2 coherence that may indicate imbalance of functional processes.Â Â